Lesson study as a tool for rebuilding teachers' practical thinking: a bridge between espoused theories and theories-in-use - Peña-Trapero, Noemí; Pérez-Gómez, Ángel Ignacio; Soto-Gómez, Encarnación; Rodriguez-Robles, Cristina; Servan-Núñez, María José (My University, 2017)
This Lesson Study forms part of the research work carried out by the Spanish team, in order to analyse the potential of this professional teacher development methodology for the reconstruction of teachers' practical thinking. It is a qualitative research process which involves the monitoring of seven infant school teachers during two school cycles. The teachers developed a Lesson Study over this period, with a practical thinking case study being carried out both before and after. This paper focuses on the Lesson Study case study. The Lesson Study was developed independently by the group of teachers, who were advised throughout by the undersigned researchers. At the same time, the researchers carried out a case study focusing on the Lesson Study being developed by the teachers. Findings/Conclusions: - From the start of the Lesson Study, we can find evidence of changes in the practical thinking of the teachers involved, which led to immediate changes in their classroom practice. - The development of the Lesson Study brought about significant reflection with regards to the Infant Education curriculum, in some cases resulting in substantial modification to the way it is implemented in their different classrooms. - The teachers pointed out the value of cooperative work on several different occasions. - They also emphasised the high level of learning they achieved by observing how their colleagues developed the lesson designed by the group using different strategies and data collection instruments, such as documentation inspired by the Reggio Emilia approach, when reflecting on their own practice. On the whole, we can state that the cooperative design work of this lesson showed the contrast between the espoused theories of the participants and their theories-in-use, conditioned fundamentally by their work contexts and previous experience. Lesson Study is a way to bring these two poles closer together, enriching teachers with strategies to help detect contradictions in their practice and to resolve them and feel more comfortable with what they do.
Keywords: Profesores - Formación profesional - Congresos; Educación infantil; Formación del profesorado; Lesson study; Conocimiento práctico